Show me the bunny - Berenson, Laurien (Berenson, Laurien. Melanie Travis mystery, 2022)
When Beatrice Gallagher, the well-respected benefactor of a new women's shelter, is murdered, Melanie Travis discovers that Beatrice wasn't the warm and generous philanthropist she appeared to be and must expose her true nature to identify a vengeful killer.